2020
DOI: 10.1186/s12887-020-02394-1
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of human milk on Bronchopulmonary dysplasia in very low birth weight infants

Abstract: Background and aim Human milk has potential protective effects against bronchopulmonary dysplasia (BPD). However, studies on the association between the dose of human milk and BPD in China are limited. This study aimed to evaluate the dose-dependent effects of human milk on BPD and other neonatal morbidities in very low birth weight (VLBW) infants. Methods This retrospective cohort study of preterm infants was conducted on preterm infants of gestat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
11
0
4
Order By: Relevance
“…A previous study indicated that HBM feeding can reduce the incidence of BPD 14,15,30 . HBM has antioxidant components, to reduce oxidative stress in premature infants and reduce the occurrence of BPD 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study indicated that HBM feeding can reduce the incidence of BPD 14,15,30 . HBM has antioxidant components, to reduce oxidative stress in premature infants and reduce the occurrence of BPD 31 .…”
Section: Discussionmentioning
confidence: 99%
“…29 A previous study indicated that HBM feeding can reduce the incidence of BPD. 14,15,30 HBM has antioxidant components, to reduce oxidative stress in premature infants and reduce the occurrence of BPD. 31 The HBM-Exo can contain large amounts of antioxidants that are protected from digestion and absorption by the gastrointestinal tract, thus entering the epithelial cells of the lung to against lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study (41) found that a considerable proportion (60.7%) of very-low-birth-weight infants without breastfeeding at discharge received high-dose breastfeeding within 14 and 28 days after birth; some had received higher amounts of MOM than infants who received exclusive and partial MOM at discharge. Early high-dose breastfeeding can significantly reduce the risk of a variety of morbidities in very-low-birth-weight patients, including LOS, NEC, and BPD, and reduce the associated costs (42)(43)(44). This emphasizes the need to collect the dose of BM (in mL/kg/d or as a proportion of total enteral feeding).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, besides its nutritional benefits, breastfeeding may have a positive impact on the incidence of BPD exploiting this and possibly other, yet undiscovered mechanisms. Indeed, Xu et al have recently reported that a daily threshold amount of 50 ml/kg/day or more of human milk in the first 4 weeks of life was associated with lower incidence of BPD ( 63 ).…”
Section: Interventionsmentioning
confidence: 99%